QUALITY OF LIFE IN DIABETIC PEOPLE CARED FOR IN A HOSPITAL IN LIMA NORTH - Ñique Oyola, Yolanda (2020)
Objectives: To determine the quality of life in diabetic people cared for in a Hospital of North Lima. Materials and methods: A quantitative, descriptive and cross-sectional study was carried out. The population consisted of older adults with type 2 diabetes, who are cared for in the endocrinology service of the Sergio Bernales National Hospital, Comas. The technique used was the survey and the instrument used was the Whoqol Bref test to evaluate the quality of life in diabetics, composed of 26 items and grouped by four domains. Results: The quality of life in patients with type 2 diabetes was medium with 97.8% (n = 135), followed by low with 1.4% (n = 2), and high with 0.7% (n = one). Regarding its dimensions, the average quality of life predominated in all, physical health with 95.7% (n = 132), psychological health 91.3% (n = 126), environment with 73.9% (n = 102) and social relationships with 50% (n = 69). The dimension with a low level of quality of life was social relationships with 47.1% (n = 65). Conclusions: The predominant quality of life was average. In relation to its four domains, the medium level predominated in all, and the dimension that obtained the highest percentage of low quality of life was the dimension of social relations.